Understanding adolescent pregnancy in Ghana: prevalence, reactions, resolution and predictors - Frank Kyei-Arthur; Sylvester Kyei-Gyamfi; Martin Wiredu Agyekum; Grace Frempong Afrifa-Anane; Kwamena Sekyi Dickson (Discover Social Science and Health)
Abstract Background Adolescence is marked by increased risky sexual activity, which could result in unintended pregnancies. Studies on adolescent pregnancy in Ghana have mainly focused on the prevalence, determinants, and effects to the detriment of the dynamics surrounding parents' and adolescents' reactions to adolescent pregnancy. This study examined the prevalence, parents' and adolescents' reactions, and pregnancy resolution among adolescents aged 10–17. In addition, it examined the predictors of adolescent pregnancy. Methods Secondary data, which used a convergent parallel mixed approach, was used to study adolescents aged 10–17 in Ghana. The quantitative data involved 382 respondents, while the qualitative data involved 15 adolescent key informants, 15 parent key informants, and 96 adolescent discussants. Descriptive statistics, Pearson's chi-square and Fisher's exact tests, and binary logistic regression were used to analyse the quantitative data. In contrast, thematic analysis was used to analyse the qualitative data. Results Slightly more than one-third of adolescents (35.3%) have ever been pregnant. Most adolescents (63.0%) affirmed that they informed their parents about their pregnancy. Adolescents indicated that parents' main reactions to adolescent pregnancy were feelings of disappointment and anger and perceiving pregnancy as normal. Adolescents expressed feelings of shock when they discovered they were pregnant. Regarding pregnancy outcomes, about 26% of adolescents aborted their pregnancy. A lack of sexual and reproductive health education and child marriage emerged as causes of adolescent pregnancy, while adolescent educational level, marital status, ecological zone, religion, and living arrangements were significant predictors of adolescent pregnancy. Conclusions This study found that adolescent pregnancy was high (35.3%). According to adolescents, some parents felt disappointed and angered, while others accepted the pregnancy of their children. Due to the high prevalence of pregnancy and lack of knowledge on sexual and reproductive health, we recommend intensifying sexual and reproductive education and services among adolescents in Ghana.